Political reform from a constitutional economics perspective: a hurdle-race ; the case of migration politics in Germany - Borella, Sara (2005)
Abstract: "This paper approaches the matter of political reform from the perspective of constitutional political economy with particular attention to the case of migration politics in Germany. That the process of policy-making has to be a constrained one is a central element of this approach, the identification of 'desired' and 'undesired' constraints its main aim. Through the metaphor of the hurdle-race it will be shown that the results of the political process depend on the rules of the game of politics on the constitutional level, but can be influenced by the contingent obstacles on the subconstitutional level. With reference to migration politics in Germany, I will argue that a separation of labour migration from other social aspects connected to migration can be useful for a more matter-of-fact discussion in this sensitive realm. The influence of subconstitutional events and factors is shown through the example of the recently approved German Immigration Act." (author's abstract)